The Urgency of Stable Coin Regulation on Crypto Assets in Indonesia - Ade Rizki Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Stablecoins, as a form of innovation in the crypto asset ecosystem, have emerged as an attractive alternative in bridging the gap between fiat currencies and highly volatile crypto assets. In Indonesia, the presence of stablecoins has sparked debate about the need for strong regulations to mitigate risks and promote sustainable growth in the crypto asset industry. This journal outlines the urgency of stablecoin regulation on crypto assets in Indonesia. We analyze the possible implications of the presence of stablecoins without adequate regulation, including their potential impact on financial market stability, consumer protection, and national security. Additionally, we investigate regulatory approaches that the Indonesian government can take to create a conducive environment for the healthy growth of the crypto asset ecosystem while safeguarding the public interest. Through a multidisciplinary approach, we present arguments supporting the importance of developing a clear and sustainable regulatory framework for stablecoins in Indonesia. We also highlight the challenges and opportunities associated with these regulations and provide insight into how appropriate regulations can provide long-term benefits for the Indonesian economy. This research aims to provide a better understanding of the complexity of stablecoin regulation in the Indonesian context, while stimulating further discussion about the regulatory direction that should be taken in the face of rapid developments in the crypto asset industry